ANALISIS KEMAMPUAN KOGNITIF SISWA SMAN 2 BANGUNTAPAN YANG MENGALAMI ADIKSI PADA GAME ONLINE - Mohammad Arif Mustofa; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The rapid development of technology has resulted in changes in several patterns of life. One of the impacts is on the development of games that now uses the internet such as online games. The ease of access to online games and better experience facilities cause many students to experience addiction to online games. The objectives of this study are to 1) Identify students' addiction to online games. 2) Examine the factors that cause students to get addicted to online games. 3) Study the impact given to the cognitive abilities of students who experience addiction to online games. The method used in this research is descriptive qualitative. The results of this research show that online games provide a sense of pleasure to players that affect their ability to control their time to play. In addition to that, online games also give a negative impact on students' cognitive abilities which cause students to have difficulty in receiving information, transformation, information, and evaluation.